Broken relationships: De-risking by correspondent banks and international trade - Lea Borchert; Ralph de Haas; Karolin Kirschenmann; Alison Schultz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
We exploit proprietary information on severed correspondent banking relationships (due to the stricter enforcement of financial crime regulation) to assess how payment disruptions impede cross-border trade. Using firm-level export data from emerging Europe, we show that when local respondent banks lose access to correspondent banking services, their corporate borrowers start to export less. This trade decline occurs on both the extensive and intensive margins, and firms only partially substitute these foregone exports with higher domestic sales. As a result, total firm revenues and employment shrink. These findings highlight an often overlooked function of global banks: providing the payment infrastructure and trade finance that enables firms in less-developed countries to export to richer parts of the world.
Keywords: F14; F15; F36; G21; G28; 330; Correspondent banking; trade finance; de-risking; global banks; international trade; anti-money laundering